Legal Status of Land Rights of the Former Eigendom Verponding After the Issuance of the Conversion Rules - Mahmuddin Mahmuddin; Herman Bakir; Faisal Santiago (Jurnal Indonesia Sosial Sains, 2023)
Beginning on September 24, 1960, there were not any more western freedoms and standard terrains. The organization no longer exists while the freedoms have been changed over by the BAL into one of the new privileges. In such manner, beginning in 1961 there could have been as of now not any land that its arrangements could be dependent upon European Verponding, Indonesian Verponding, and Lanrente or Land Expense. The assessment endorsements that existed and were held by individuals around then and were not detailed for substitution of new privileges under the UUPA, were still as Eigendom Verponding. In any case, in all actuality, there are still holders of land privileges who after September 24, 1980, still have confirmation of responsibility for freedoms as western privileges and standard freedoms that poor person been changed over, which will create legitimate issues assuming that these are not directed in regulation. To expect lawful issues that emerge because of changes in guidelines in the land area, the public authority through transformation guidelines reaffirmed the lapse of privileges to the place that is known for beginning of the Change of Western Freedoms on September 24, 1980, which is likewise the standard framed in the BAL., to end the legitimacy of the excess Western privileges to land in Indonesia with every one of attributes are not by Pancasila and the 1945 Constitution